Hydrothermal Synthesis of Hematite (α-Fe2O3) from Indonesia Iron Sand - Furqonul Hakin Al Hadi; Tanti Haryati; Novita Andarini; Suwardiyanto; Sulistiyo, Yudi Aris (Indonesian Chimica Letters, 2023)
High potency of Indonesian iron sand can be optimized by transforming to valuable iron oxide product namely Hematite (α-Fe2O3). Hydrothermal synthesis was carried out to transform iron oxide phase to hematite that can be analyzed by x-ray diffraction method. Utilization of ion sand as raw material produced multyphase in product reaction, while  the usage of Fe(OH)x that extracted from iron sand attained high purity of hematite. The best conditions of reaction were at 160 oC for 24 h. Higher temperature and longer time reaction transformed α- α-Fe2O3 to be γ-Al2O3 and Fe3O4 as more stable phase.